The non-metathetic role of Grubbs’ carbene complexes: From hydrogen-free reduction of α,β-unsaturated alkenes to solid-supported sequential cross-metathesis/reduction - Poeylaut Palena, Andrés Alberto (2011)
An efficient and high-yielding “hydrogen-free” reduction of α,β-unsaturated alkenes was carried out employing Grubbs' catalyst in a non-metathetic role and Et3SiH. Conditions were optimized under microwave irradiation. Application to the solid-phase organic synthesis allows a facile construction of sp3–sp3 carbon bonds through a sequential cross metathesis/olefin reduction.